INFLUENCE OF GLOBALIZATION PROCESSES AND THE FOURTH INDUSTRIAL REVOLUTION ON THE DEVELOPMENT OF FOREIGN ECONOMIC ACTIVITY OF KAZAKHSTAN - Gussenov Barkhudar; Dyrka Stefan (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with the features of foreign economic activity management. One of the issues discussed and insufficiently studied in the scientific literature is the management of foreign economic activity. The article attempts to study the essence of this type of activity. Based on the system-process approach, the authors describe the main elements of foreign economic activity management and specify the content of its stages. The article reveals the features of foreign economic development strategy formation. The necessity of application of technologies and innovative methods of management when entering the international markets is proved. Also, the article considers the interpretation of the fourth industrial revolution and its impact on the development of economic sectors of the Republic of Kazakhstan. The article describes the main aspects and potential of foreign trade characteristics of both enterprises and regions of the Republic. The influence of globalization processes and the fourth industrial revolution on the socio – economic development of the country is described.